Prenatal diagnosis of a compound heterozygous variation in the FBXL4 gene by trio-WES and imaging monitoring: a case report - Zhai, Yujia; Chen, Jing; Yang, Shuo; Wang, He; Xiao, Yuanyuan; Liu, Shanling (Frontiers in Genetics, 2025)
F-box and leucine-rich repeat protein 4 (FBXL4) plays a crucial role in mitochondrial bioenergetics, mitochondrial DNA (mtDNA) maintenance, and mitochondrial dynamics. The variations in the FBXL4 gene can give rise to encephalomyopathy mitochondrial DNA depletion syndrome-13 (MTDPS13) characterized by the reduction of mtDNA copy number, leading to deficiencies in mitochondrial functions, which is a serious and rare autosomal recessive genetic disorder. Patients with FBXL4 variations are usually diagnosed due to the emergence of symptoms in the early stages of life. Commonly observed are lactic acidemia, developmental retardation, and hypotonia. A portion of patients may be accompanied by comorbidities such as cardiovascular diseases, epilepsy, ophthalmopathy, hearing impairment, and movement disorders. Currently, there have been no reported cases of prenatal diagnosis for FBXL4 gene variations. Here, we report for the first time the prenatal diagnosis of a fetus with a compound heterozygous mutation in the FBXL4 gene (NM_012160.5: c.1288C>T, p. Arg430* and c.518_523del, p. Glu173_Leu175delinsVal) by trio-WES, the nonsense mutation (c.1288C>T) was reported only once in an unrelated individual and no detailed clinical phenotype; the deletion mutation (c.518_523del) has not been reported yet. Additionally, we monitor prenatal phenotypes of fetus at different stages of pregnancy using ultrasound and magnetic resonance imaging (MRI), present prenatally with nuchal translucency (NT) thickening and progressive brain developmental abnormalities. Our report indicates that the application of trio whole exome sequencing (trio-WES) and imaging monitoring can facilitate prenatal diagnosis of FBXL4 gene-related MTDPS13, and this will modify the decision-making process for couples with FBXL4 variations.